Luminance and timing control during visual presentation of natural scenes. (October 2022) - De Cesarei, Andrea; Marzocchi, Michele; Codispoti, Maurizio
Graphical abstract: Abstract: In the study of visual cognition, accurate control of stimulus presentation is of primary importance yet is complicated by hardware malfunctioning, software variability, and visual materials used. Here, we describe VISTO 2.0, a low-cost and open-source device which is capable to measure the timing and temporal luminance profile of visual stimuli. This device represents a major improvement over VISTO (De Cesarei, Marzocchi, & Loftus, 2021), as it is only sensitive to a light spectrum in the visible range, is easier to assemble, and has a modular design that can be extended to other sensory modalities.